PERFORMANCE OF KENBRO CHICKEN FED COWPEA (Vigna unguiculata): SOYBEAN (Glycine max) DIETS AT VARIOUS REPLACEMENT LEVELS - Katumo, Mulwa Albert; Mworia, Dr. Mugambi; Ncene, Dr. William (IJRDO- Journal of Educational Research, 2017)
The demand for poultry meat has tremendously over the years, and the high cost of Soybeanmeal necessitates the evaluation of locally available protein ingredients which can be used assubstitutes for conventional protein meals. This research sough to study the effect of substitutingSoybean meal with Cowpea meal on feed intake, weight gain, feed conversion ratio and cost perkg weight gain in Kenbro chicks. The results showed that there was no significant difference infeed intake, while there was a significant difference in total weight gain (g), and feed conversionratio. There was equally no significant difference production cost of one kg live weight and thusthe study concludes that Cowpea meal can replace up to 50 % SBM (14 % of the diet) as analternative cheaper plant protein source in Kenbro diets at 3-9 weeks of age this can be anexcellent source of dietary protein.